INTRA-VAGINAL ISOSORBIDE MONO-NITRATE IN ADDITION TO MISOPROSTOL VERSUS MISOPROSTOL ALONE FOR SECOND TRIMESTER TERMINATION OF PREGNANCY (The Research of Medical Science Review, 2025)
Background: Second trimester pregnancy termination, typically occurring between 13 and 26 weeks of gestation, accounts for approximately 10–15% of all induced abortions. Compared to first trimester procedures, second trimester abortions are associated with increased risks of complications and maternal mortality. Common reasons for second trimester termination include late diagnosis of fetal anomalies, intrauterine fetal demise, delayed access to abortion services, and socioeconomic constraints. While dilation and evacuation (D&E) remains the most common method, medical abortion with misoprostol—often combined with mifepristone—is used in early second trimester cases, although its efficacy declines with advancing gestation.Objective: To compare the efficacy and safety of intravaginal isosorbide mononitrate in combination with misoprostol versus misoprostol alone for second trimester termination of pregnancy.Methods: This randomized controlled trial was conducted at the Department of Obstetrics and Gynecology, Pakistan Institute of Medical Sciences (PIMS), Islamabad. A total of 216 women undergoing second trimester pregnancy termination were randomized into two equal groups. Group A received intravaginal isosorbide mononitrate followed by misoprostol, while Group B received misoprostol alone. Efficacy outcomes included complete abortion rate, number of misoprostol doses, need for surgical evacuation, estimated blood loss, and duration of hospital stay. Adverse effects and complications were also recorded and analyzed.Results: Group A had a significantly higher complete abortion rate (87% vs 77.8%, p < 0.05), required fewer misoprostol doses (3.2 ± 0.9 vs 4.1 ± 1.1; p < 0.001), and showed a lower need for surgical evacuation (16.7% vs 27.8%; p = 0.04). Mean blood loss and hospital stay were significantly reduced in Group A. Side effects such as headache and palpitations were more frequent in Group A but were generally mild and self-limiting.Conclusion:The addition of intravaginal isosorbide mononitrate to misoprostol significantly enhances the efficacy of second trimester pregnancy termination, reduces the need for surgical intervention, and shortens hospital stay, with an acceptable safety profile.